The effects of EU and EEA law in national legal systems: Trends and challenges - Birna Guðmundsdóttir 1992- (2019)
In this thesis, the effect of EU law in national legal systems and EEA law in the Icelandic legal system are observed with specific regard to the requirements flowing from the principle of primacy and effectiveness of EU and EEA law. During these observations, specific attention is given to the limitations or problems arising when EU and EEA law are given effect domestically. The thesis consists of three main chapters, not counting the introduction and final conclusion. The first chapter covers the general principles of primacy and effectiveness of EU law and the reception of these principles by constitutional courts of the EU Member States. During that, the restrictions of Member States constitutional courts are examined and whether any new problems regarding the effect of EU law are on the rise.The second chapter examines the effect of EEA law in the Icelandic legal system and the requirements stemming from the principles of primacy and effectiveness of EEA law. Additionally, the limitations of the effect of EEA law in Iceland are looked into. In that regard, the disagreement about the Kolbeinsson case is highlighted, along with the different legislative tools of ESA and the EU Commission regarding infringement proceedings and the theoretical discussion about whether an amendment of the Constitution is needed to give international law, the EEA Agreement especially, adequate effect in the Icelandic legal system. In the third chapter, current tensions and challenges regarding the effect of EEA law are examined. Three fundamental factors falling under the subject will be observed. Firstly, the “unique” step of ESA but in 2017 the Authority commenced infringement proceedings against Iceland for failing to adopt the requirements of Protocol 35 which prescribes that implemented EEA rules should take priority over conflicting national provisions. Secondly, the effects of this failure in terms of Advisory Opinions from the EFTA Court are discussed briefly, and thirdly, the effect of EEA law as observed in the thesis ...